The Phenomenon of Tadz Tadhad (Antonyms) in the Qur'an - Fitriani, Namiyah; Habib, Ikhwanul; Handayani, Rima Ayu; Yafi, Ahmad Fauzan; Asy-Syahidah, Qorina Himmati (Anjasmoro: Islamic Interdisciplinary Journal, 2025)
The Qur'an, as the divine revelation to Prophet Muhammad, employs Arabic language, necessitating a deep understanding of Arabic linguistics, including semantics (ʿilm al-dalālah). This study explores the phenomenon of tadhadh (antonyms) in the Qur'an from a semantic perspective, aiming to identify and analyze antonymic word pairs and their implications in Qur'anic discourse. Using a qualitative approach with library research methods, the study examines Qur'anic verses, classical and modern linguistic sources, and scholarly works on Arabic semantics. The findings reveal five types of antonyms based on Al-Khammas’ classification: (1) absolute antonyms (taḍādd ḥādd), (2) graded antonyms (taḍādd mutadarrij), (3) converse antonyms (taḍādd ʿaks), (4) perpendicular antonyms (taḍādd ʿamūdī), and (5) straight-line antonyms (taḍādd imtidādī). Examples from various Qur'anic verses illustrate how these antonyms enhance rhetorical and theological depth. The study underscores the importance of semantic analysis in Qur'anic exegesis, contributing to broader linguistic and interpretive studies of the Qur'an.